Analisis Selisih PPh Terutang, Ekualisasi Pembelian, dan Biaya Sehubungan dengan Jasa dalam Menanggapi SP2DK - Nur Aini, Evinda Dwi; Muslimin (TEMA, 2024)
This study aims to analyze the resolution of responses to SP2DK received by PT JKL. The research method applied is a qualitative techniques with case study approach. Sources of information used come from primary data, namely interviews and direct observation, as well as secondary data such as working papers, financial reports, and relevant documents. The research findings reveal discrepancies in the calculation of payable income tax due to calculation errors that did not include several components of income and other expenses in the calculation of gross circulation. The difference in total purchases on the Corporate Income Tax Annual Return (SPT Tahunan PPh Badan) with the total acquisitions on the VAT Periodic Return (SPT Masa PPN) occurs because the Corporate Income Tax Annual Return includes purchase components from non-taxable suppliers (non-PKP). Additionally, the discrepancy in the value related to services on the Corporate Income Tax Annual Return and the Periodic Income Tax Return 23/26 (SPT Masa PPh 23/26) is caused by the taxable expenses under Article 21 income tax on the Corporate Income Tax Annual Return and the reporting of expenses in the May 2020 Periodic Income Tax Return 23, which was deducted not in the month the services were completed.   Abstrak Penelitian ini dimaksudkan untuk menganalisis penyelesaian tanggapan atas SP2DK yang diterima oleh PT JKL. Metode penelitian yang diterapkan adalah teknik kualitatif dengan pendekatan studi kasus. Sumber Informasi yang dipakai berasal dari data primer yaitu, wawancara dan observasi langsung, serta data sekunder seperti kertas kerja laporan keuangan dan dokumen relevan. Hasil penelitian mengungkapkan bahwa terdapat selisih perhitungan PPh terutang karena kesalahan hitung dengan tidak memasukkan beberapa komponen pendapatan dan biaya lain-lain ke dalam perhitungan peredaran bruto. Selisih total pembelian pada SPT Tahunan PPh Badan dengan total perolehan yang ada pada SPT Masa PPN terjadi karena pada SPT Tahunan PPh Badan terdapat komponen pembelian dari supplier non-PKP. Selain itu, selisih nilai sehubungan dengan jasa pada SPT Tahunan PPh Badan dan SPT Masa PPh 23/26 disebabkan oleh biaya objek pajak PPh Pasal 21 pada SPT Tahunan PPh Badan dan pelaporan biaya di SPT PPh 23 bulan Mei 2020 yang dipotong bukan pada bulan saat jasa diselesaikan.